Private Madrasah Quality Improvement Strategy: Competency-Based Madrasah Principal Selection Policy at the Ministry of Religious Affairs - Ika Shohihah (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This policy paper describes that low quality of student achievement in private Islamic schools is a serious problem rooted in the low quality of leadership of the principals. This policy analysis identifies that the problem is caused by recruitment and assignment processes that are not competency-based, as well as weak competency standards for private Islamic school principals. This policy paper uses a qualitative method with a descriptive analysis approach and literature study, integrating data from official reports, scientific journals, and government regulations. The problem analysis is conducted through the USG (Urgency, Seriousness, Growth) framework to prioritize the root causes. Theoretical support is obtained from Transformational Leadership Theory, Human Capital Theory, and Principal-Agent Theory. In addition, conceptual support is based on the Instructional Leadership Concept and the Change Management Concept. Based on this analysis, three alternative regulatory policies are proposed: (1) revision of the Minister of Religious Affairs Regulation number 24 of 2018 which is competency-based in accordance with the provisions of Article 6 paragraph 1, (2) issuance of a decree by the Director General of Islamic Education (Pendis) regulating an independent and transparent selection team, and (3) issuance of technical instructions on a periodic performance evaluation system. These three alternatives are then analyzed using William N. Dunn's scoring theory to determine their feasibility and effectiveness. The analysis results show that the revision of the PMA has the highest score, followed by the issuance of the decree of the Director General of Islamic Education regulating the selection team, which is considered the most effective and worthy solution to be recommended to the Ministry of Religion in an effort to improve the quality of education in private madrasas.